2021
DOI: 10.18203/issn.2454-2156.intjscirep20210548
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gas flaring on communities in Delta region of Nigeria, narrative review part 1: environmental health perspective

Abstract: <p class="abstract">Gas flaring is the combustion of associated gas from crude-oil exploitation and exploration operations and occurs in refineries, oil wells, oil rigs by fiery of the gas. Nigeria is one of the main producers of gas in the world and oil exploration activities have occasioned high rate of gas flaring because of poor enforcement of anti-gas flaring laws by the regulatory authorities. Gas flaring comes with serious environmental concern because it is a major source of air pollution with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Mandatory environmental sustainability measures are compared between environmentally sensitive sectors like oil and gas and less sensitive sectors (Babangida & Kao'je, 2023). Research on the impact of gas flaring on communities underscores the risks associated with this practice and the need for mitigation strategies (Nkemdilim et al, 2021). Evaluating the economic and social value from gas flaring is crucial for addressing environmental concerns and maximizing benefits (Romsom & McPhail, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mandatory environmental sustainability measures are compared between environmentally sensitive sectors like oil and gas and less sensitive sectors (Babangida & Kao'je, 2023). Research on the impact of gas flaring on communities underscores the risks associated with this practice and the need for mitigation strategies (Nkemdilim et al, 2021). Evaluating the economic and social value from gas flaring is crucial for addressing environmental concerns and maximizing benefits (Romsom & McPhail, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gas flaring activities is undertaken as a way to remove dangerous gases with lower harm to the environment by the multinational oil companies, safely regulating pressure in chemical plant, as well as handling natural gas releases in wells but the monitoring of this flare gas is a challenge in Nigeria, making it difficult to quantify the gases released during exploration and exploitation of petroleum product. According to [7], many of the flares in Niger Delta region do not have flare meters, leading to uncertainties on reported flared estimates of the total volume of gas. Authors like [8] [9] revealed that operators sometimes benefit from inadequate reporting of flare gas volume through financial, commercial and reputational favours, re-emphasizing the need for adequate monitoring, however, [10] recommends that ultrasonic meters are the most suitable type of meter for flare volume measurement and have been proposed for use in Nigeria.…”
Section: Concepts Of Gas Flare On Human Life and Wellbeingmentioning
confidence: 99%
“…The oil company still continue to engage in gas flaring because of the absence of plants and machinery to harness the reinjection of these gases during the production process. At the moment of new regulation is being approved known as flare Gas (prevention of waste and pollution) regulations 2018 (Obi, et al, 2021).…”
Section: Associated Gas Re-injection Actmentioning
confidence: 99%